Single Spatiotemporal Display: Documentary Photography Of Pua Kumbu - Hashim, Khairul Hazrin; Dolah, Jasni (2016)

(untitled)
The paper is an articulation of the objective, process, and output of a photo-mosaic display of a documentary photography of Pua Kumbu. The photo-mosaic display is a combination of multiple-sized images printed on a single wall, viewed together with slide-shows on monitors. It discusses the objective of incorporating still with time-based images on one spatiotemporal platform, making it a unique viewing experience, through an explorative and experimental method of photographic image consumption [1]. Pua Kumbu is a traditionally woven textile of the Iban people of Sarawak and Borneo. It is a meticulous and complicated process using natural dyes and weaving techniques passed down from generations and practiced by the women of the longhouses. The documentary photography is an extensive coverage of the whole process of producing this craft, from preparing the yarn, through the making of the dyes to lastly, the weaving. The documentation also covers other contextual elements such as the environment, the weavers, and rituals. As in the principles of documentary photography, the images are a series of photographs, non-directed or staged, and underlined with a social investigation, specific to a thematic spectatorial expectation [2]. In this case to bring forth the hidden and almost unknown aspects and elements in the traditional weaving craft of the textile. The paper illustrates the photographer’s point-of-views, from pre-photography work and literature review, photographing, post-processing and selection of images, design process of the display, and final installation. The photo-mosaic display was a feature in The Textile Tales of Pua Kumbu, A Polysensory and Intermedia Exhibition [3] in June 2015 at the Universiti Malaya Art Gallery, Kuala Lumpur